Eksplorasi Potensi Kehidupan di Planet Lain dalam Alam Semesta - Shika Andari; Khairun Nisa; Vina Aulia; Angelina Sipayung; Muhammad Arif; Elsa Kardiana (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study explores the possibility of extraterrestrial life by examining environmental factors that could support survival, such as the availability of liquid water, a balanced atmosphere, and access to energy. The investigative approach was carried out through the integration of various data sources, including telescope observations, spacecraft exploration, and simulation modeling of planetary climate conditions. The findings reveal that a number of exoplanets within the habitable zone have environmental parameters that could potentially support life, although further research is still needed to uncover the biochemical mechanisms and adaptability of life in unusual environments. This study makes an important contribution to the development of astrobiology and expands the opportunities for exploring life beyond our planet, while offering a new understanding of the possibility of life in the vast universe.